PENINGKATAN LIFE SKILL PADA IBU-IBU LPKK DI DUSUN PAJANGAN BERBAH MELALUI PELATIHAN BROWNIES BEKATUL - Andayani, Sri Wahyu; Setyaningsih, Rina; Wati, Ika Wahyu Kusuma; Kurniawan, Roni (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Increased life skills for mothers in Pajangan sub-village through rice bran training. The purpose of the training is to improve life skills in the Pajangan sub-village, especially in food products using local bran ingredients. Rice bran has a variety of nutrients including antioxidants containing tocopherol, vitamin E and vitamin B15. These compounds play a role to reduce blood cholesterol levels, prevent cancer and facilitate hormonal secretions. Besides rice, rice husks or rice bran are not only sold to feed livestock, but are developed to make quality and quality products, but also can increase income and improve the living standards of LPKK women in Pajangan Berbah Hamlet, Sleman. The kinds of products we make are wet brownies and dry brownies. Abdimas is held in the Pajangan hamlet hall, Berbah Sleman. This activity was carried out for two days, namely the preparation phase on the first day and the implementation and socialization on the second day with a total of twelve hours of activity time. The target of this activity is LPKK women in the Pajangan Berbah Sleman. This activity is carried out using lecture, demonstration, training and practice methods. The resulting output is an increase in life skills through the skills to make bran brownies is a weekly newpepper.